Abstract 4137644: Association of Prolonged QTc with Development of Heart Failure after Hematopoietic Stem Cell Transplantation - Shu, Lihua; Vasbinder, Alexi; Catalan, Tonimarie; Machado, Kristen; Ismail, Anis; Hutten, Christina; Pizzo, Ian; Huang, Yiyuan; Blakely, Pennelope; Banerjee, Mousumi; Leja, Monika; Hayek, Salim (Circulation (New York, N.Y.), 2024)
Background: Use of hematopoietic stem cell transplantation (HSCT) continues to rise in the United States, particularly in older age groups; however, HSCT is associated with various cardiovascular complications including heart failure (HF). We sought to examine whether prolonged QTc prior to HSCT was associated with the risk of HF post-HSCT. Methods: We used data from the Cardiovascular Registry in Bone Marrow Transplantation (CARE-BMT) study, a multicenter observational study of adult patients (aged ≥18 years) who underwent autologous/allogeneic HSCT for malignant or nonmalignant bone marrow disorders at the University of Michigan Health System (UMHS) and Rush University Medical Center (RUMC) between 2008-2019. In this analysis, only patients from the UMHS site were included (n=2,435). Baseline electrocardiogram (EKG) data were recorded prior to transplant (median (IQR) 14 (3, 30) days). QTc prolongation was defined per CTCAE grading criteria as Normal (<440ms), Grade 1 (440-480ms), and Grade ≥2 (>480ms). The primary outcome was new-onset HF defined as a diagnosis documented by health care providers after the date of hospitalization for HSCT. Analyses were conducted using a Fine-Gray model adjusted for the pre-HSCT CARE-BMT cardiovascular risk score. Results: Of the 2,435 patients (mean age at HSCT 55±13.4 years; 59.7% male; 90.5% White), 534 (21.9%) had long QTc pre-HSCT. Of those, 440 were Grade 1 and 94 were Grade ≥2. In all, 138 HF events occurred over median period of 2.3 (1.0-5.3) years. The 5-year cumulative incidence of HF was 5.0% in patients with normal QTc, 8.4% in patients with Grade 1 QTc prolongation, and 19.0% in patients with Grade ≥2 QTc prolongation (Figure). Patients with Grade 1 and Grade ≥2 prolongation had a 1.57 (95% CI: 1.05, 2.33) and 2.71 (95% CI: 1.51, 4.86) times higher risk of HF, respectively, compared to those with normal QTc. Conclusions: In this contemporary cohort of adult HSCT patients, those with QTc prolongation prior to HSCT had a higher incidence of HF compared to normal QTc, with greater degree of prolongation associated with higher risk. These findings highlight the importance of accounting for the QTc as part of the pre-transplant cardiovascular evaluation